(untitled) (Journal of Transport System Engineering, 2023)
The implementation of electric vehicles introduces new tribological challenges, specifically for bearing systems. Up to 90% of the electric motor rolling bearing is reported to be lubricated by grease. However, the improper selection of grease types can result in premature rupture of the lubricant film due to excessive heat generation during operation. This paper focuses on analysing the frictional behaviour of various commercially available greases intended for use in bearing systems of passenger cars, considering the same mineral base oil with different types of thickener. To study the frictional and wear behaviour, a ball-on-disc friction tester is used to test the selected greases. Experimentally, the studies greases showed similar Stribeck curve trend showing that thickener used in grease plays crucial role in influencing the friction and wear properties. Thus, present study helps to provide knowledge for optimisation of grease for electric motors.